FAKTOR-FAKTOR YANG MEMPENGARUHI PERSONAL AUDITOR INDEPENDEN TERHADAP PERILAKU DISFUNGSIONAL AUDIT (Studi empiris pada Auditor di KAP Pekanbaru dan Padang) - Rizki Pratiwi; Azwir Nasir; Devi Safitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
Audit dysfunctional behavior is behavior that justifies the occurrence of irregularities in the audit, which resulted in a decrease of audit quality, both directly and indirectly. Such as manipulation by the auditors in the audit assignment in order to achieve the target of individual work. This study aims to examine and analyze the effect of locus of control, work experience, underreporting of time and job stress on dysfunctional behavior audit. The study population is the auditor who works at KAP Pekanbaru and Padang. The number of respondents of the study was 65 copies, only 50 copies that can be processed. The sample is determined by purposive sampling method, data analysis techniques using Structural Equation Model (SEM) with the help SmartPLS version 3.0 was used to test whether the independent variables affect the dependent variable. The result of this study shows that the locus of control, work experience, underreporting of time, job stres have the possitive to the dysfunctional audit behavior. The results showed that the locus of control, work experience, underreporting of time and job stress affect the audit dysfunctional behavior in KAP pekanbaru and padang. The results also showed the contribution of independent variable influence on the dependent variable is equal to 92%. While the remaining 8% is influenced by other variables not included in this SmartPLS model.KeyWords : Locus of Control, Work Experience, Underreporting of Time, Job Stress.